Stereotactic Ablative Radiotherapy for a Lung Metastasis in a Child With Ewing's Sarcoma. Issue 6 (August 2016) - Amsbaugh, Mark J.; Bertke, Matthew; Cheerva, Alexandra; Silverman, Craig; Dunlap, Neal
Abstract : Stereotactic ablative radiotherapy delivers a high dose of radiation to a small volume over several fractions. Although most commonly used as a treatment alternative to surgery in adult patients with primary lung cancer, its use has now been reported in children with metastatic disease to the lungs. We present the case of a child treated with stereotactic ablative radiotherapy to pulmonary metastases in preparation for a salvage stem cell transplant. The patient was treated to a dominant pulmonary nodule and successfully received his stem cell transplant, however he developed clinical and radiographic findings consistent with pneumonitis several months after treatment.